Implementation Of Performance Management At Isana Delimart Supermarket Using Deming Model Tanjungpinang - Juleha Juleha; Sairin Prayoga; Septia Maharani; Siti Nordiana; Satriadi Satriadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this research is to find out about the implementation of existing performance at ISANA DELIMART supermarket using the Deming model in terms of planning, implementation, evaluation, and corrective action. The research method used to complete this research is a qualitative method with a descriptive approach, which involves interviews conducted with the ISANA DELIMART supermarket, observations made on performance management at the ISANA DELIMART supermarket, and documentation as a data collection method. The population in the study was the manager and all employees of ISANA DELIMART supermarket, while the sample used was the manager and 1 employee of ISANA DELIMART supermarket. The results of this study indicate that ISANA DELIMART supermarket has not implemented performance management properly, all because there are still problems that occur in implementing management which can affect performance management at ISANA DELIMART supermarket. So the final result of the research can be done by ISANA DELIMART supermarket by improving the way of working in the implementation of its planning.